Role of CC chemokine CCL6/C10 as a monocyte chemoattractant in a murine acute peritonitis - Andrew M. LaFleur; Nicholas W. Lukacs; Steven L. Kunkel; Akihiro Matsukawa (Mediators of Inflammation)
THE aim of this study was to determine the role of CC chemokine CCL6/C10 in acute inflammation. Intraperitoneal injection of thioglycollate increased peritoneal CCL6, which peaked at 4 h and remained elevated at 48 h. Neutralization of CCL6 significantly inhibited the macrophage infiltration (34-48% reduction), but not other cell types, without decreasing the other CC chemokines known to attract monocytes/macrophages. CCL6 was expressed in peripheral eosinophils and elicited macrophages, but not in elicited neutrophils. Peritoneal CCL6 level was not decreased in granulocyte-depleted mice where eosinophil influx was significantly impaired. Thus, CCL6 appears to contribute to the macrophage infiltration that is independent of other CC chemokines. Eosinophils pre-store CCL6, but do not release CCL6 in the peritoneum in this model of inflammation.